Bending of a composite material strip with curved structure in the geometrically nonlinear statement - Yahnioglu, N; Selim, S (CONSULTANTS BUREAU, 2000)
To date, bending problems for strips or plates made of composite materials with curved structure have been investigated only in the linear statement. However, in many cases, the necessity arises to investigate the corresponding bending problems in the geometrically nonlinear statement. Therefore, in the present paper, some binding problems for a composite strip with a periodically curved structure is investigated in such a statement using the exact nonlinear equations of elasticity theory in Lagrangian coordinates. The numerical results are obtained by employing the FEM with the use of the Newton-Raphson and the Modified Newton-Raphson algorithms.
Keywords: composite strip; curved structure; bending; geometrical nonlinearity; finite element method; Mechanics; Materials Science; Polymer Science